TRANSLANGUAGING PRACTICES IN SONGS BY INDONESIAN SINGERS - Eka Margianti Sagimin; Ariyanti Sapitri (Universitas Pamulang, 2023)
The practice of translanguaging in Indonesian songs by Indonesian singers is the primary focus of this paper. The objectives of the study are to categorize the types of translanguaging strategies used in songs, analyze how translanguaging is employed, and investigate why Indonesian artists use translanguaging in their songs. Using the qualitative method, this current study presents the translanguaging practice of the selected singer and its song. Weird Genius and Sara Fajira's song